Rhizoctonia solani Kühn Pathophysiology: Status and Prospects of Sheath Blight Disease Management in Rice - Senapati, Manoranjan; Tiwari, Ajit; Sharma, Neha; Chandra, Priya; Bashyal, Bishnu Maya; Ellur, Ranjith Kumar; Bhowmick, Prolay Kumar; Bollinedi, Haritha; Vinod, K. K.; Singh, Ashok Kumar; Krishnan, S. Gopala (Frontiers in Plant Science, 2022)
Sheath blight caused by necrotrophic fungus Rhizoctonia solani Kühn is one of the most serious diseases of rice. Use of high yielding semi dwarf cultivars with dense planting and a high dose of nitrogenous fertilizers accentuates the incidence of sheath blight in rice. Its diverse host range and ability to remain dormant during unfavourable conditions make the pathogen more difficult to manage. As there are no sources of complete resistance, management through chemical control has been the most adopted method for sheath blight management. In this review, we provide an up-to-date comprehensive description of host-pathogen interactions, various control measures such as cultural, chemical, and biological as well as utilizing host plant resistance. The section on utilizing host plant resistance includes identification of resistant sources, mapping QTLs and their validation, identification of candidate gene(s) and their introgression through marker-assisted selection. Advances and prospects of sheath blight management through biotechnological approaches such as overexpression of genes and gene silencing for transgenic development against R. solani are also discussed.